Postnatal development of inhibitory synaptic transmission in the anterior piriform cortex. Issue 71 (December 2018) - Pardo, Grace Violeta Espinoza; Lucion, Aldo Bolten; Calcagnotto, Maria Elisa
Highlights: Inhibitory synaptic transmission in aPC of developing normal and naris occluded rats were measured. GABAA R-mediated inhibition on L2/3 neurons of aPC increase with postnatal age. Average of mIPSC kinetics in L2/3 neurons of aPC decreases with postnatal age. Inhibitory synaptic transmission development is slight affected by early partial olfactory deprivation. Abstract: The morphological and functional development of inhibitory circuit in the anterior piriform cortex (aPC) during the first three postnatal weeks may be crucial for the development of odor preference learning in infant rodents. As first step toward testing this hypothesis, we examined the normal development of GABAergic synaptic transmission in the aPC of rat pups during the postnatal days (P) 5–8 and 14-17. Whole cell patch-clamp recordings of layer 2/3 (L2/3) aPC pyramidal cells revealed a significant increase in spontaneous (sIPSC) and miniature (mIPSC) inhibitory postsynaptic current frequencies and a decrease in mIPSC rise and decay-time constant at P14-P17. Moreover, as the development of neocortical inhibitory circuit can be driven by sensory experience, we recorded sIPSC and mIPSC onto L2/3 aPC pyramidal cells from unilateral naris-occluded animals. Early partial olfactory deprivation caused by naris occlusion do not affected the course of age-dependent increase IPSC frequency onto L2/3 aPC pyramidal cell. However, this age-dependent increase of sIPSC and mIPSC frequencies were lower on aPC pyramidal cells ipsilateral to the occlusion side. In addition, the age-dependent increase in sIPSC frequency and amplitude were more pronounced on aPC pyramidal cells contralateral to the occlusion. While mIPSC kinetics were not affected by age or olfactory deprivation, at P5-P8, the sIPSC decay-time constant on aPC pyramidal cells of both hemispheres of naris-occluded animals were significantly higher when compared to sham. These results demonstrated that the GABAergic synaptic transmission on the aPC changed during postnatal development by increasing inhibitory inputs on L2/3 pyramidal cells, with increment in frequency of both sIPSC and mIPSC and faster kinetics of mIPSC. Our data suggested that the maturation of GABAergic synaptic transmission was little affected by early partial olfactory deprivation. These results could contribute to unravel the mechanisms underlying the development of odor processing and olfactory preference learning.